2022
DOI: 10.3390/w14040619
|View full text |Cite
|
Sign up to set email alerts
|

Application of DPSIR and Tobit Models in Assessing Freshwater Ecosystems: The Case of Lake Malombe, Malawi

Abstract: Inland freshwater shallow lake ecosystem degradation is indistinctly intertwined with human-induced factors and climate variability. Changes in climate and human-induced factors significantly influence the state of lake ecosystems. This study provides evidence of the driver, pressure, state, impact, and response (DPSIR) indicators for freshwater lake ecosystem dynamics, taking Lake Malombe in Malawi as a case study. We used the DPSIR framework and Tobit model to achieve the study’s objectives. The study’s find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 96 publications
(139 reference statements)
0
14
0
Order By: Relevance
“…The outcome of this research is the development of holistic and efficient LULC change and CC management approaches that are "bottom-up" driven, i.e., from communities to government policy and decision-makers (Bell and Morse 2001 ). This is in contrast to common top-down approaches in Uganda, where government through decision and policy-makers prefer to use expert, scientific/reductionist legislation and regulations with less consultation with local communities, which often leads to counterproductive efforts in dealing with LULC change and CC impacts (Wantzen et al 2019 ; Kosamu et al 2022 ). Most research studies have shown that both approaches are ineffective in dealing with the impacts independently (Hägerstrand 2001 ; Grêt-Regamey et al 2013 ; Ricaurte et al 2014 ; Wantzen et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The outcome of this research is the development of holistic and efficient LULC change and CC management approaches that are "bottom-up" driven, i.e., from communities to government policy and decision-makers (Bell and Morse 2001 ). This is in contrast to common top-down approaches in Uganda, where government through decision and policy-makers prefer to use expert, scientific/reductionist legislation and regulations with less consultation with local communities, which often leads to counterproductive efforts in dealing with LULC change and CC impacts (Wantzen et al 2019 ; Kosamu et al 2022 ). Most research studies have shown that both approaches are ineffective in dealing with the impacts independently (Hägerstrand 2001 ; Grêt-Regamey et al 2013 ; Ricaurte et al 2014 ; Wantzen et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Like other inland freshwater shallow lakes in Africa, such as Lake Chilwa, Chiuta, Kyoga, Rukwa, Baringo, Chiuta, Mweru Wa Ntipa, Naivasha, Awassa, Langano, and Victoria, Lake Malombe is thoroughly mixed, somewhat turbid, highly productive and climate-sensitive (Makwinja et al, 2022a;Obubu et al 2022). The lake is near Mangochi town in the northern part (Kosamu et al, 2022;Makwinja et al, 2022c). Increased human activities, over-exploitation, climatic drivers, settlements, and unsustainable farming activities overstress the catchment, subsequently bringing nutrient load into the lake (Makwinja et al 2021b).…”
Section: Study Areamentioning
confidence: 99%
“…The monitoring efforts also cost the United States of America about US$ 1 million per event, with US$ 50,000 per affected area. In Lake Malombe, Njaya et al (2011) evidenced the collapse of Oreochromis spp in the 1990s, Bagrus meridionalis and Clarias spp in 2000, large demersal haplochromine cichlids in 1986, Labeo mesops in 1996, Copadichromis virginalis in 1994 and overall, the whole lake shery in 2016, which among other factors was attributed to profound ecological changes of the lake(Kosamu et al, 2022) Kosamu et al (2022). also noted that increased disease outbreaks such as dysentery, schistosomiasis, and diarrhea…”
mentioning
confidence: 99%
“…Table 1 summarises the contents of the papers [1][2][3][4][5][6][7][8][9][10] submitted to this Special Issue into categories of global region, type of water body and model or modelling approach used. From North America, modelling exercises on rivers in Canada have been reported, particularly the Athabasca [9] and South Saskatchewan [1] rivers in western Canada.…”
mentioning
confidence: 99%
“…One study from Africa (Lake Malombe in Malawi) [6] and another from Nordic Europe (various rivers in Norway, Sweden, Finland, eastern Germany and Poland) [10] are included in this Special Issue. The first study links overarching demographic, socio-economic, climatic and other factors to the lake's ecosystem health.…”
mentioning
confidence: 99%